Stress Reduction Techniques for Health Care Providers Dealing With Severe Coronavirus Infections (SARS, MERS, and COVID-19): A Rapid Review - Callus, Edward; Bassola, Barbara; Fiolo, Valentina; Bertoldo, Enrico G.; Pagliuca, Silvana; Lusignani, Maura (Frontiers in Psychology, 2020)
Objective—A rapid review was conducted to identify the most effective stress reduction techniques for health care providers dealing with patients infected with severe coronavirus (SARS, MERS COVID-19) Methods— PubMed, PsychInfo, Embase and CINAHL databases were searched to identify relevant studies. Searches were restricted by date (2000 until present). All empirical quantitative and qualitative studies in which relaxation techniques of various types implemented on health care providers caring for patients during severe coronavirus pandemics, and articles which consider the implementation of mental health care services considered to be pertinent, such as commentaries were included. Results—14 studies met the selection criteria, most of which were recommendations. Only 1 study described an intervention, which was digital were user satisfaction was measured. In the recommendations both organizational and individual self-care interventions were suggested. Conclusions— Further research is necessary to establish tailor made effective stress reduction interventions for this population, during these challenging and particular times.